A 1-Year Lifestyle Intervention for Weight Loss in Individuals With Type 2 Diabetes Reduces High C-Reactive Protein Levels and Identifies Metabolic Predictors of Change: From the Look AHEAD (Action for Health in Diabetes) study - Belalcazar, L. Maria (American Diabetes Association, 2010)
OBJECTIVE: We examined whether a 1-year intensive lifestyle intervention (ILI) for weight loss reduced elevated high-sensitivity C-reactive protein (hs-CRP) levels in obese individuals with diabetes and identified metabolic and fitness predictors of hs-CRP change. RESEARCH DESIGN AND METHODS: Look AHEAD (Action for Health in Diabetes) is an ongoing multicenter clinical trial examining the effects of weight loss achieved through ILI on cardiovascular events and overall mortality in obese/overweight adults with type 2 diabetes. We report on 1,759 Look AHEAD participants who had hs-CRP and fitness data at baseline and 1 year. Subjects were randomly assigned to ILI or to usual care (diabetes support and education [DSE]). ILI involved frequent counseling to increase moderate-intensity exercise to 175 min/week, reduce caloric and saturated fat intake, and change macronutrient composition to improve glycemic control. RESULTS: ILI reduced median hs-CRP by 43.6% from baseline to 1 year, compared with a 16.7% reduction with DSE (P < 0.001). ILI decreased weight (8.8%), A1C (0.7%), and triglycerides (17%) and increased fitness (19%) and HDL cholesterol (7.5%) (P < 0.0001 vs. changes with DSE). Changes in adiposity and glucose control with ILI remained independent predictors of hs-CRP change at 1 year (P < 0.0001 for each) after adjustment for demographics, smoking, cardiovascular history, statin and thiazolidinedione use, and changes in fitness and lipid control. Neither statin nor insulin therapy modified the association between ILI and hs-CRP. CONCLUSIONS: A 1-year lifestyle intervention for weight loss in obese individuals with diabetes was associated with substantial reductions in hs-CRP. Improved glycemic control and reduced adiposity had comparable effects on hs-CRP change.